2020
DOI: 10.3389/fnins.2020.00014
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Stage Classification Using Time-Frequency Spectra From Consecutive Multi-Time Points

Abstract: Sleep stage classification is an open challenge in the field of sleep research. Considering the relatively small size of datasets used by previous studies, in this paper we used the Sleep Heart Health Study dataset from the National Sleep Research Resource database. A long short-term memory (LSTM) network using a time-frequency spectra of several consecutive 30 s time points as an input was used to perform the sleep stage classification. Four classical convolutional neural networks (CNNs) using a time-frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 28 publications
1
23
1
Order By: Relevance
“…We observed different results compared to our previous research that used the same data [ 35 ] and, despite a smaller sample, the only difference came from the unconventional referencing to P3 P4 for Epoc +. Considering those previous results, the increased significance with Epoc + in the present study does not mean that EGI is less performant, but only that the re-referencing largely shapes the signal.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…We observed different results compared to our previous research that used the same data [ 35 ] and, despite a smaller sample, the only difference came from the unconventional referencing to P3 P4 for Epoc +. Considering those previous results, the increased significance with Epoc + in the present study does not mean that EGI is less performant, but only that the re-referencing largely shapes the signal.…”
Section: Discussioncontrasting
confidence: 99%
“…These result are also concordant (for both devices) with physiological data from Rickard [ 53 ] and Salimpoor [ 54 ], suggesting that an increasing pleasure and the onset of chills produce an activation of the peripheral system with higher skin conductance responses/levels and higher heart rate levels. Our previous research did not demonstrate the relevance of approach withdrawal analysis with alpha asymmetry calculations with the EGI gold-standard setup [ 35 ]. Consequently, we chose to analyse only alpha and theta PSD measures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, we traditionally conceive PpS as the space directly surrounding our body [ 36 , 37 ], which serves as a privileged interface between the body and the external world [ 36 ]. In accordance with this point of view, electro-physiological studies on monkey brain [ 38 ] and neuroscientific research in humans [ 39 , 40 ] showed that multisensory integration processes are gradually more powerful when they occur closer to the body. In particular, visuo-tactile interactions seem to be particularly sensitive to the spatial distance at which visual stimuli are positioned while the concurrent tactile input is delivered [ 39 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 79%